Cholesterol in colorectal cancer: an essential but tumorigenic precursor? - He, Xing; Lan, Huanrong; Jin, Ketao; Liu, Fanlong (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is one of the most lethal human malignancies, and with the growth of societies and lifestyle changes, the rate of people suffering from it increases yearly. Important factors such as genetics, family history, nutrition, lifestyle, smoking, and alcohol can play a significant role in increasing susceptibility to this cancer. On the other hand, the metabolism of several macromolecules is also involved in the fate of tumors and immune cells. The evidence discloses that cholesterol and its metabolism can play a role in the pathogenesis of several cancers because there appears to be an association between cholesterol levels and CRC, and cholesterol-lowering drugs may reduce the risk. Furthermore, changes or mutations of some involved genes in cholesterol metabolism, such as CYP7A1 as well as signaling pathways, such as mitogen-activated protein kinase (MAPK), can play a role in CRC pathogenesis. This review summarized and discussed the role of cholesterol in the pathogenesis of CRC as well as available cholesterol-related therapeutic approaches in CRC.